The Effect of Somethinc Product Review on TikTok on Brand Awarenes in Medan City - Putri, Shalli Anggia; Pohan, Syafruddin; Nasution, Chairunnisah Rahmi (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2025)
This research examines how Somethinc Brand Product Review on Tiktok affects FISIP USU students' brand awareness. This quantitative correlational study included 2,311 female Faculty of Social and Political Sciences students. The Slovin formula was used to sample 95 persons with 10% precision and 90% confidence. Proportional stratified random and purposive sampling are used in this investigation. We collected data via questionnaires. Researchers used validity, reliability, single table, cross table, and Spearman's level coefficient hypothesis testing. FISIP USU students like Somethinc Brand product evaluations on Tiktok, and most have top-of-mind brand awareness. Hypothesis testing demonstrates a correlation coefficient of 0.578 between Somethinc Brand product reviews on Tiktok and brand awareness among FISIP USU students. According to the correlation determination test, the Somethinc Brand product review on Tiktok increases brand awareness among FISIP USU students by 33%. Penelitian ini meneliti bagaimana Ulasan Produk Merek Somethinc di Tiktok mempengaruhi kesadaran merek mahasiswa FISIP USU. Penelitian kuantitatif korelasional ini melibatkan 2.311 mahasiswa FISIP USU. Rumus Slovin digunakan untuk mengambil sampel sebanyak 95 orang dengan presisi 10% dan tingkat kepercayaan 90%. Pengambilan sampel secara acak bertingkat proporsional dan purposive sampling digunakan dalam penelitian ini. Kami mengumpulkan data melalui kuesioner. Para peneliti menggunakan uji validitas, reliabilitas, tabel tunggal, tabel silang, dan uji hipotesis koefisien tingkat Spearman. Mahasiswa FISIP USU menyukai evaluasi produk Somethinc Brand di Tiktok, dan sebagian besar memiliki kesadaran merek yang tinggi. Pengujian hipotesis menunjukkan koefisien korelasi sebesar 0,578 antara ulasan produk Somethinc Brand di Tiktok dengan kesadaran merek di kalangan mahasiswa FISIP USU. Berdasarkan uji determinasi korelasi, ulasan produk Somethinc Brand di Tiktok meningkatkan kesadaran merek di kalangan mahasiswa FISIP USU sebesar 33%.